Long-term dysbiosis and fluctuations of gut microbiome in antibiotic treated preterm infants - Murat Cetinbas; Julie Thai; Evgenia Filatava; Katherine E. Gregory; Ruslan I. Sadreyev (iScience, 2023)
Summary: Postnatal acquisition of the microbiome is critical to infant health. In preterm infants, empiric use of antibiotics is common, with significant health consequences. To understand the influence of antibiotics on acquisition of the microbiome over time, we longitudinally profiled microbial 16S rRNA in the stool of 79 preterm infants during their hospitalization in the intensive care unit and compared antibiotic treated and untreated infants. Despite similar clinical presentation, antibiotic treated infants had strong deviations in the content, diversity, and most dramatically, temporal stability of their microbiome. Dysbiosis and fluctuations of microbiome content persisted long after antibiotic exposure, up to hospital discharge. Microbiome diversity was dominated by a few common bacteria consistent among all infants. Our findings may inform clinical practice related to antibiotic use and targeted microbial interventions aimed at overcoming the adverse influence of antibiotics on the microbiome of preterm infants at specific developmental time points.